THE POSITIVE EFFECT OF TOTAL QUALITY MANAGEMENT (TQM) ON THE ACHIEVEMENT OF CLINICAL QUALITY INDICATORS IN INPATIENT UNITS OF TANGERANG DISTRICT HOSPITAL ASSOCIATED BY NURSE PERFORMANCE - Heri Danuri; M. Natsir Nugroho; Yanuar Ramadhan (Dinasti Publisher, 2021)
An indicator of clinical quality is a valid and reliable quantitative process related to one or more performance dimensions. The achievement of clinical quality indicators is strongly influenced by the performance performed by a nurse and is supported by a quality program known as Total Quality Management (TQM). The poor achievement of clinical quality indicators in the inpatient unit at the Tangerang District Hospital is a strong reason to find out what factors can influence it and find a solution. This study aims to analyze the effect of TQM on the achievement of clinical quality indicators in the inpatient unit of Tangerang District Hospital mediated by the performance of nurses on 217 implementing nurses through a causal descriptive quantitative approach and using SEM analysis. Data collection techniques use primary and secondary data. The results obtained: (1) TQM has a positive effect on the achievement of clinical quality indicators mediated by the performance of the nurses; (2) TQM has a positive effect on the achievement of clinical quality indicators; (3) the performance of nurses has a positive effect on the achievement of clinical quality indicators; (4) TQM has a positive effect on nurse performance.